MTHFR and MTRR gene polymorphisms in patients with chronic hepatitis B virus infections in Zigong, Sichuan Province - Shunhua Qiu; Lifen Jin; Dan Yang; Dewen Zhang (Annals of Human Biology)
Background Chronic hepatitis B virus (HBV) infection is a severe disease affecting the physical and economic well-being of patients. The relationship between polymorphisms in the MTHFR gene and disease progression following HBV infection remains a controversial topic.Aim To study MTHFR and MTRR gene polymorphisms in patients with chronic HBV infections in Zigong, Sichuan Province.Subjects and methods One hundred and ninety-one patients with chronic HBV infections were divided into three groups: the chronic hepatitis B (CHB) group (n = 71), the hepatitis B-induced liver cirrhosis (LC) group (n = 56), and the hepatitis B-related primary liver cancer (PLC) group (n = 64). The gene polymorphisms were detected using the PCR-melt curve method and analysed.Results The distributions of MTHFR C677T (CC: 41.2% vs. 41.8%; CT: 50% vs. 45.5%; TT: 8.8% vs. 12.7%; p = 0.714), MTHFR A1298C (AA: 70.6% vs. 72.7%; AC: 26.5% vs. 25.5%; CC: 2.9% vs. 1.8%; p = 1.000), and MTRR A66G (AA: 58.1% vs. 65.5%; AG: 39.0% vs. 29.1%; 2.9% vs. 5.5%; p = 0.353) genetic polymorphisms did not vary between male and female patients from Zigong. In addition, there were no differences in the distributions of MTHFR C677T (CC: 43.4% vs. 38.8%; CT: 49.1% vs. 48.2%; TT: 7.5% vs. 12.9%; p = 0.444), MTHFR A1298C (AA: 76.4% vs. 64.7%; AC: 20.8% vs. 32.9%; CC: 2.8% vs. 2.4%; p = 0.155), and MTRR A66G (AA: 62.3% vs. 57.6%; AG: 34.0% vs. 38.8%; 3.8% vs. 3.5%; p = 0.353) genetic polymorphisms between the patients <60 and >60 years of age. The distributions of MTHFR C677T (CHB vs. LC, p = 0.888; CHB vs. PLC, p = 0.661; PLC vs. LC, p = 0.926), MTHFR A1298C (CHB vs. LC, p = 0.12; CHB vs. PLC, p = 0.263; PLC vs. LC, p = 0.550), and MTRR A66G (CHB vs. LC, p = 0.955; CHB vs. PLC, p = 0.645; PLC vs. LC, p = 0.355) gene polymorphisms were comparable between the CHB, LC, and PLC groups.Conclusion The distributions of MTHFR and MRRR genetic polymorphisms in the population with HBV infections in Zigong, Sichuan Province did not differ in age and sex. The MTHFR and MRRR genetic polymorphisms were comparable between the CHB, LC, and PLC groups.